Primary and Secondary Immune Responses to Keyhole Limpet Hemocyanin in Rats After Infusion of Hemoglobin Vesicle, an Artificial Oxygen Carrier. Issue 3 (22nd August 2013) - Fujihara, Mitsuhiro; Takahashi, Daisuke; Abe, Hideki; Sakai, Hiromi; Horinouchi, Hirohisa; Kobayashi, Koichi; Ikeda, Hisami; Azuma, Hiroshi
Abstract Hemoglobin vesicles (HbVs), artificial oxygen carriers encapsulating concentrated Hb solution on phospholipid vesicles (liposomes), are promising candidates for clinically useful transfusion. Although HbV infusion transiently suppressed the proliferative response of rat splenic T‐cells to concanavalin A or keyhole limpet hemocyanin (KLH), a T‐cell‐dependent antigen, in ex vivo culture conditions, HbV infusion did not affect the primary IgG antibody response. We extended our assessment of the effects of HbV infusion on the systemic immune response using primary and secondary responses to KLH in rats. We observed that the generation of primary anti‐KLH IgM antibody in HbV‐infused rats was not suppressed but was instead higher than those in saline‐infused rats. Furthermore, HbV infusion did not suppress the increase of IgG subclass of KLH antibody in secondary response. The T cell response to KLH of bulk spleen cells, as derived from 2–3 months after secondary KLH immunization, was unaffected by infusion of HbV, suggesting that HbV loading has no suppressive effect on homeostatic survival of memory T‐cells against KLH. These results indicate that HbV is highly biocompatible in systemic immune responses in rats.